In vitro production of the factors effective in the transfer of experimental autoimmune aspermatogenesis - Pokorná, Z; Pekárek, J; Svejcar, J (Folia biologica, 1975)
We studied the biological effects of the factors released into the culture medium by the lymphocytes from animals sensitized with testicular antigen. The supernatants from cultures of these lymphocytes were active in vitro in the migration inhibition tests because they transferred the sensitivity to normal spleen cells. In vivo, they transferred aspermatogenesis in the allogeneic and xenogeneic system. The results suggest a specific effect on the behaviour of macrophages rather than a direct cytotoxic effect of the active factors.
Keywords: Antigens; In Vitro Techniques; antigeny; tvorba protilátek; Guinea Pigs; Male; Macrophage Migration-Inhibitory Factors; inhibiční faktory migrace makrofágů; Cell Migration Inhibition; mužské pohlaví; techniky in vitro; testis; Cytotoxicity Tests, Immunologic; Antibody Formation; morčata; Macrophages; aktivace lymfocytů; Testis; zvířata; Lymphocyte Activation; Spermatogenesis; autoprotilátky; makrofágy; inhibice migrace buněk; Spermatozoa; spermatogeneze; Autoantibodies; spermie; cytotoxické testy imunologické; Animals